Peran Perspektif Gender dalam Penyusunan Kebijakan Pemidanaan: Studi Kualitatif terhadap Kasus Kekerasan Berbasis Gender - Arda, Ravi; Yanti, Desi (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
Gender-Based Violence (GBV) remains a critical issue in Indonesia, with a significant increase in reported cases over the past five years. Despite the implementation of the Sexual Violence Crime Law (UU TPKS) as a progressive step toward victim protection, challenges persist in the law enforcement process, particularly in integrating gender perspectives into the criminal justice system. This study aims to analyze the role of gender perspectives in sentencing policies for GBV perpetrators in Indonesia and compare them with more progressive legal frameworks in other countries. Using a qualitative approach with phenomenological methods, the study examines national regulations, judicial decisions, and stakeholder interviews, including victims, law enforcement officers, and legal experts. The findings indicate that while the number of GBV cases reported has increased from 15,200 in 2018 to 35,200 in 2023, only 10% of reported cases resulted in convictions. This reflects systemic weaknesses, such as insufficient legal enforcement, limited gender-sensitive training among judicial actors, and societal stigma against victims. Additionally, comparative analysis with countries like Sweden and Canada suggests that more inclusive and restorative justice approaches can enhance victim protection and reduce recidivism rates. This study contributes to the discourse on criminal law reform by highlighting the need for stronger regulatory frameworks, improved law enforcement mechanisms, and technological innovations in reporting and case management. The findings provide policy recommendations for strengthening Indonesia’s GBV sentencing policies through a gender-sensitive and victim-oriented approach.